(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Currently, information technologies play a significant role in the development and improvement of the efficiency of the healthcare system. The process of digitalization in the field of medicine organizes the exchange of information, treatment, and diagnostic processes in healthcare institutions based on modern technologies. Digital databases, electronic medical records, telemedicine, diagnostic systems using artificial intelligence, and mobile health applications are the main directions of this process.